2018
DOI: 10.18632/oncotarget.25986
|View full text |Cite
|
Sign up to set email alerts
|

miR-193b and miR-30c-1* inhibit, whereas miR-576-5p enhances melanoma cell invasion in vitro

Abstract: In cancer cells, microRNAs (miRNAs) are often aberrantly expressed resulting in impaired mRNA translation. In this study we show that miR-193b and miR-30c-1* inhibit, whereas miR-576-5p accelerates invasion of various human melanoma cell lines. Using Boyden chamber invasion assays the effect of selected miRNAs on the invasive capacity of various human melanoma cell lines was analyzed. Upon gene expression profiling performed on transfected A375 cells, CTGF, THBS1, STMN1, BCL9, RAC1 and MCL1 were identified as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 59 publications
0
14
0
Order By: Relevance
“…It is a well‐accepted fact that the aberrant expression of miRNAs play significant roles in the carcinogenesis and progression of human cancers . Therefore, in‐depth understanding of the roles of miRNAs shall provide new dimension into molecular mechanism involved in the tumor formation and growth of cancer as well for the development of novel therapeutic strategies .…”
Section: Resultsmentioning
confidence: 99%
“…It is a well‐accepted fact that the aberrant expression of miRNAs play significant roles in the carcinogenesis and progression of human cancers . Therefore, in‐depth understanding of the roles of miRNAs shall provide new dimension into molecular mechanism involved in the tumor formation and growth of cancer as well for the development of novel therapeutic strategies .…”
Section: Resultsmentioning
confidence: 99%
“…In the past, miRNAs were also considered as non-functional RNA, but more and more studies have shown that miRNAs are involved in various biological functions of cells (Tarallo et al 2019;Xu et al 2020;Vignard et al 2020). Many studies have shown that miRNA-576-5p plays an important role in a variety of cancers, such as esophageal cancer (Zhang et al 2019), colorectal cancer (Makondi et al 2019) and melanoma (Kordaß et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, miRNAs have been reported to serve as effective biomarkers for the early diagnosis and prognosis of patients with cancer ( 10 ). A previous study demonstrated that miR-576-5p might be a potential tumor-promoting oncomiR in several types of human tumor ( 11 ). Kordass et al ( 11 ) reported that miR-576-5p enhances the invasion of melanoma cells in vitro .…”
Section: Introductionmentioning
confidence: 99%
“…A previous study demonstrated that miR-576-5p might be a potential tumor-promoting oncomiR in several types of human tumor ( 11 ). Kordass et al ( 11 ) reported that miR-576-5p enhances the invasion of melanoma cells in vitro . In addition, miR-576-5p was also found to be upregulated in esophageal cancer, where it was found to be involved in cancer cell migration and invasion, suggesting that it might serve as a predictor of cancer prognosis ( 12 , 13 ).…”
Section: Introductionmentioning
confidence: 99%